Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Ludo dalam Meningkatkan Minat Belajar Siswa di SMA Negeri 1 Darussalam - *Putri Rahmadani Desky; Husaini Ibrahim; Sufandi Iswanto (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2022)
This research is entitled "Application of Cooperative Learning Model Type Teams Games Tournament (TGT) Assisted by Ludo Media in Increasing Students' Interest in Learning at SMA Negeri 1 Darussalam Aceh Besar". The problem in this study is the lack of student interest in learning. This study aims to determine the learning interest of class XI IPS students with the TGT type cooperative model assisted by Ludo media. The type of research used in this research is descriptive with a qualitative approach. The subjects of this study were students of class XI IPS, totaling 16 students. Data collection is done by observation and questionnaires. The results of observing student activities in the implementation of learning are 80% in the very good category. Student interest in the application of the Teams Games Tournament (TGT) cooperative learning model assisted by ludo media 22.25% answered strongly agree, 49.5% who hesitated answered agree, 18.7% answered doubtful, 6.7% answered disagree and 2.7% who answered strongly disagree with the proportion of 80% in the very good category. So it can be said that in the process of applying the TGT type cooperative model assisted by Ludo Media, it can increase students' interest in learning.